Increasing technology adoption in Latin America and the Caribbean - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
IRRI works towards farmer-to-farmer exchange in incorporating new production strategies. It highlights farmer participation in designing and running these programs. Having had successful projects in improved crop management in the region, CIAT, through the FLAR initiative, is an important partner in diagnosing key management factors for improvement, identifying innovative farmers to conduct initial validation plots, establishing  farmers’  groups  around these farmer-leaders, and conducting intensive training of farmers and technicians.